Lobar Collapse and Obliteration of Air Bronchogram Allowing Early Diagnosis of Endobronchial Aspergillus Infection following Hematopoietic Stem Cell Transplantation. (10th December 2014) - Thompson, Elizabeth; Thyagarajan, Manigandan S.; Johnson, Elizabeth; Weeden, David; Morgan, Mary; Groves, Sarah J.; Steward, Colin G.
Abstract : Endobronchial fungal infection (EBFI) is notoriously difficult to diagnose early since it may present few systemic features and does not cause characteristic parenchymal lesions on lung CT scanning. We report a 9-year-old girl who suffered extended neutropenia following graft failure after haematopoietic stem cell transplantation (HSCT) for severe aplastic anaemia. CT scan prior to retransplantation was normal despite persistent cough but lobar collapse was shown on repeat scan 16 days later. The probable diagnosis of EBFI (later proven on bronchoscopy) was only suspected when subsequent chest X-ray (CXR) demonstrated lack of an air bronchogram in the partially collapsed lung. Early radiological suspicion resulted in multiagent antifungal therapy followed by delayed lobectomy, and led to this being the first reported case of Aspergillus EBFI not to result in respiratory failure.